Linking SLAMF1 to autophagy and sensitivity to therapy in chronic lymphocytic leukemia - Cinzia Bologna; Silvia Deaglio (Molecular & Cellular Oncology, 2018)
We recently reported that expression of the costimulatory molecule and microbial sensor SLAMF1 (signaling lymphocytic activation molecule family 1, also known as CD150) is lost in chronic lymphocytic leukemia (CLL) patients characterized by a shorter overall survival. SLAMF1 modulates CLL responses to chemokines and regulates autophagy. Loss of SLAMF1 renders CLL cells relatively unresponsive to autophagy-inducing drugs, including B-cell CLL/lymphoma 2 (BCL2) inhibitors.